Penerapan Model Project Based Learning Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Matematika Kelas VI SDN 39 Mataram - Alpiati, Novi; Nur’Asiah, Nur’Asiah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study aims to determine the learning outcomes of students in grade VI SDN 39 Mataram Mathematics through the application of a project based learning model. This research is a class action research (CAR) which was carried out in two cycles. This research was conducted in class VI of SDN 39 Mataram for the 2022/2023 academic year with a total of 39 students. The research instrument was in the form of a test of learning outcomes. The results showed that the learning outcomes of students experienced an increase from pre-cycle to cycle II. The learning outcomes of students before the action was carried out there were 9 students who achieved KKM (KKM= 75) with an average learning achievement score of 64, then in the implementation of cycle I obtained 13 students who had reached KKM with an average learning achievement score of 74, and in the implementation of cycle II, 29 students had achieved KKM with an average learning achievement score of 81. Based on the results of this study, it was concluded that the application of the project-based learning model could improve the learning outcomes of class VI students at SDN 39 Mataram.